2022
DOI: 10.1111/dth.15360
|View full text |Cite
|
Sign up to set email alerts
|

Figurate purpuric eruption post‐COVID‐19 vaccination

Abstract: Dear Editor, COVID-19 pandemic had spread rapidly all around the world leading to variety of manifestations that ranged from being asymptomatic to death. 1 While COVID-19 vaccination has played a very important role in ending this pandemic, adverse reactions are increasingly reported including cutaneous ones. Injection-site local reactions are among the most common reported cutaneous manifestations, followed by urticaria, pityriasis rosea-like lesions, and pernio/chilblains. 2 Herein we report a post-vaccine u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In multiple studies, histopathologic evaluation of vasculitis lesions showed leukocyte infiltration into the endothelia resulting in inflammation and swelling. [9][10][11][12][13][14][15][16][17][18][19] Subsequently, perivascular mixed lymphocytes, neutrophils, and occasional eosinophils plus marked debris and red blood cells (RBCs) extravasations were reported, which was consistent with leukocytoclastic vasculitis 10,11,13,14,16,[18][19][20][21][22][23][24][25][26][27] ; these findings were also observed in 2 other cases: a figurate purpuric eruption 28 and a pigmented purpuric dermatosis. 29 Furthermore, immunofluorescence microscopy was performed on some samples, and deposition of C3, fibrin, fibrinogen, immunoglobulin M, and IgA were reported.…”
Section: Vasculitismentioning
confidence: 79%
“…In multiple studies, histopathologic evaluation of vasculitis lesions showed leukocyte infiltration into the endothelia resulting in inflammation and swelling. [9][10][11][12][13][14][15][16][17][18][19] Subsequently, perivascular mixed lymphocytes, neutrophils, and occasional eosinophils plus marked debris and red blood cells (RBCs) extravasations were reported, which was consistent with leukocytoclastic vasculitis 10,11,13,14,16,[18][19][20][21][22][23][24][25][26][27] ; these findings were also observed in 2 other cases: a figurate purpuric eruption 28 and a pigmented purpuric dermatosis. 29 Furthermore, immunofluorescence microscopy was performed on some samples, and deposition of C3, fibrin, fibrinogen, immunoglobulin M, and IgA were reported.…”
Section: Vasculitismentioning
confidence: 79%
“…Either IgE mediated or IgG is the reaction from hypersensitivity after vaccine administration. It is caused by complement-mediated anaphylactic and delayed T-cell-mediated reactions IgE (Namazi et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Morbilliform eruptions and urticaria are the main reason for hypersensitivity reactions primarily (Namazi et al, 2022). Three of four patients developed recurrent delayed urticaria after the second dose of the COVID-19 vaccine.…”
Section: B Pathophysiology Of Urticaria Post-covid-19 Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation